Examine entrepreneurial motivations and entrepreneurial success in homestay program: Evidence from a developing region in Sabah, Malaysia - Kelvin Yong; Tam Yin Ling @ Adeline Tam; Priscilla Shak; Kamsilawati Kamlun; Rafidah Binti Nordin; Brahim Chekima; Rudy Ansar; Suddin Lada; Lim Ming Fook (GMP Press & Printing Co, 2024)
This study explores the relationship between entrepreneurial motivation, driven by both push and pull factors, and the entrepreneurial success of homestay entrepreneurs in Sabah, Malaysia. It aims to identify the research gap in our understanding of homestay programs. In addition, there is limited research exploring the factors that contribute to the entrepreneurial success of Sabah homestay. Sabah is currently the second-highest revenue generator for homestay in Malaysia. However, despite its growth, the homestay industry in Sabah faces challenges that can lead entrepreneurs to leave homestay programs. The resource-based view (RBV) framework was used to analyze the relationship between entrepreneurial motivation and entrepreneurial success. Data were purposively sampled from active homestay entrepreneurs, with a sample size estimated using the G-Power approach. A total of 110 valid questionnaires were collected, and the study employed PLS- SEM techniques for analysis. The findings of the study reveal a significant positive correlation between both pull and push factors and entrepreneurial success. These findings can provide useful managerial applications for related government agencies and universities. The government can support Sabah's homestay industry by providing financial aid, enhancing infrastructure, and organizing talks. Combined with the region's ecotourism potential, could attract younger participants to join the homestay program.